How to diagnose and treat secondary forms of vasculitis. - Luqmani, R; Pathare, S; Kwok-Fai, T (2005)
Vasculitis is considered to be secondary when it arises either in the context of a pre-existing connective tissue disease, as a result of direct infection with a limited range of organisms, especially viruses, or when it arises in response to exposure to a number of medications. Rheumatoid vasculitis is probably the most widely recognised form of secondary vasculitis, and in this article we review the incidence, clinical features and management of this condition. Infections may either trigger or cause some types of vasculitis. Drug therapy is a common cause of limited forms of vasculitis and may enhance our understanding of the mechanism of these diseases. The premature development of atherosclerosis in patients with existing connective tissue diseases or indeed primary vasculitis has been recognised for some time, and the underlying mechanisms are currently being studied. An appreciation of the complex and varied pathophysiology of secondary vasculitis may further our understanding of primary vasculitis.